Pengaruh Berbagai Ekstrak Metanol Tumbuhan terhadap Mortalitas Juvenil Instar-2 dan Penetasan Telur Nematoda Sista Kentang (Globodera rostochiensis) - Iis Nur Asyiah; Elin Yulinah; Mumu Sutisna; Buchari Buchari (Universitas Gadjah Mada, 2005)
The research was conducted to know the influence of methanol extracts from 19 plant species to the second-stage juvenil (J2) mortality and to the hatching of the potato cyst nematode, Globodera rostochiensis, the new pest of potato in Indonesia. The research was conducted by using complete random design, where each treatment was repeated 3 times. Cyst hatching was conducted by using ZnSO4 10-2 M. Data obtained to be analyzed with the ANOVA and continued with the DMRT 5%. The result indicated that from 19 species of examined plant, clove flower and leaf methanol extract with concentration 10.000 ppm inflicted 100% and 96,7% J2 mortality and others inflicted <50% 12 mortality. Clove flower and leaf methanol extract permanently inhibited of cyst hatching, methanol extract of Andrograpis puniculata, Capsium frutescens, Chrysanthemum sp., and Allium sativum inhibited of cyst hatching non permanently, while other plants extract methanol didn't inhibit of cyst hatching.